GEOPHYSICAL ANALYSIS OF FRACTURED BASEMENT IN MALAY BASIN USING MULTI-ATTRIBUTES METHOD - B MOHD NAZRI, MUHAMMAD REDZUAN IKHBAL (Universiti Teknologi PETRONAS, 2015)
Since the major hydrocarbon discovery in the fractured granite basement of Cuu Long basin in offshore Vietnam, fractured basement have been extensively explored by major oil and gas industry players. Thus, Anding field of Malay Basin has been extensively study to assess its capability of being a hydrocarbon play as its neighboring basins which is Cuu Long basin. Although lithology of the fractured basement of Malay Basin comprised of meta-sediments, volcanic, granite and carbonates which clearly lacks in primary porosity, the fractures that present in the basement might increase the porosity by providing secondary porosity which enables the basement to be a potential reservoir. Reservoir within the fractured basement also fulfill the petroleum system criteria by having their own source rock, seal and reservoir with increased porosity due to presence of fracture. In addition, the migration path can be defined by the open fractures that act as conduit for hydrocarbon flow. In order to assess the potential basement play is to characterize the fractures network by applying seismic attributes technique. Structural interpretation and attributes analysis using attributes i.e. variance, coherence, curvature were being applied on both data set; vintage and advanced data set. Advanced data set yield a better results in terms of both structural interpretation and attributes application.